PEMANFAATAN LIMBAH JAGUNG PAKAN SEBAGAI POC PADA TANAMAN JAGUNG MANIS - Tuti Herlinawati; Muhammad Rizal; Jamilatul Amalia; Mahdiannoor Mahdiannoor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
Feed corn is a new commodity developed in Balangan Regency. Some parts of this feed corn are not used and are just left alone by farmers who are classified as agricultural waste. This feed corn plant waste be used as a LOF. This LOF is used to increase the..growth of sweet corn plants. This study aims (i) effect LOF waste corn feed on sweet corn plants. (ii)the best concentration. This research was conducted in Tabuan Village, Halong District, Balangan Regency, South Kalimantan Province from June - August 2021, using a single factor RBD. The factors  studied  were the application of..LOF..from corn waste feed (W) as much as 5 levels namely w1 = 28.5 cc. plot-1 , w2 = 85.5 cc.plot-1, w3 = 142.5 cc.plot-1, w4 = 199.5 cc. plot-1, w5 = 256.5 cc.plot-1. The.results .this.study..the LOF treatment of feed corn waste had a significant effect on plant variables aged 28 DAP, but had no effect on plant variables aged 14 and 21 DAP, length of cob with and without husks, the weight of cobs with and without husks. The best feeding corn waste POC was l3 (142.5 cc.plot-1) of plant height and stem diameter at 28 DAP with l1 (28.5 cc.plot-1) on the variable number of leaves at 28 DAP.